Geological values of lava caves in Krongno Volcano Geopark, Dak Nong, Vietnam - Phuc, La The; Tachihara, Hiroshi; Honda, Tsutomu; Tuat, Luong Thi; Thom, Bui Van; Hoang, Nguyen; Chikano, Yuriko; Yoshida, Katsuji; Tung, Nguyen Thanh; Danh, Pham Ngoc; Hung, Nguyen Ba; Duc, Tran Minh; et al. (Vietnam Journal of Earth Sciences, 2018)
The paper presents the initial results of the study of volcanic cave system and its typical formations in Krongno Volcano Geopark (KVG), Dak Nong, Vietnam. The volcanic caves have been discovered since 2007, under UNESCO sponsored the scientific project, are seen as unique geological heritages. The collaborative surveys and studies between Vietnamese geologists and the members of the Non-Profit Organization, Vulcanospeleological Society of Japan have discovered and surveyed 45 caves, and detailed mapping 20 caves. Using a complex of adequate methods, especially Remote Sensing image interpretation method, Surveying and mapping lava cave method, K/Ar dating isotopic analytical method and Current methodology, the studies aim to affirm endogenous origin of the lava cave system, the formation mechanism, as well as the typical formations of the caves. Up to date, the lava caves and interior formation in lava caves in KVG have been examined and evaluated in term of geological nature and recognized as pillar geological heritages of the Geopark.References Allred K., AllredC., 1997. Development and morphology of Kazumura Cave, Hawaii. Journal of Cave and Karst Studies, 59(2), 67-80.Allred K., Allred C., 1997. Tubular lava stalactites and other related segregations. Journal of Cave and Karst Studies, 60(3), 131-140.Barnabás Korbély, 2014. Diverse volcanic features as dominant landscape elements and pillars of geotourism in the Bakony-Balaton Geopark, Hungary. Abstract Book Workshop “Geoparks in volcanic areas: sustainable development strategies”, October 29th to November 1st, 2014. Terceira and Graciosa Islands, Azores Global Geopark, 35-38.Bird Deanne K., et al., 2014. Southern Iceland: Volcanoes, Tourism and Volcanic Risk Reduction.In Volcanic Tourist Destinations. Springer, Editors: Erfurt-Cooper, Patricia (Ed.). ISBN: 978-3-642-16190-2, 35-46. Cooper Malcolm J.M., 2014. Volcanic National Parks in Japan.In Volcanic Tourist Destinations. Springer, Editors: Erfurt-Cooper, Patricia (Ed.). ISBN: 978-3-642-16190-2, 231-246.Dave Bunnell, 2014. The virtual lava cave Created: August 4, 2000.Last update: December 16, 2014. Reviewed by Kevin & Carlene Allred. Available at:<http://www.goodearthgraphics.com/virtual_tube/virtube.html). Date accessed: 02 May 2018.Gadányi P., 2010. Formation, types and morphology of basalt lava caves. PhD. thesises. University of Pécs Faculty of Natural Sciences Doctoral School of Earth Sciences, Hungary, 1-19.Gaki-Papanastassiou, Kalliopi, et al., 2014. Volcano Tourism in Greece: Two Case Studies of Volcanic Islands.In Volcanic Tourist Destinations. Springer, Editors: Erfurt-Cooper, Patricia (Ed.). ISBN: 978-3-642-16190-2, 69-87.Honda T., Tachihara H., 2015. Vietnam Volcanic Cave Survey. e-NEWSLETTER, UIS Commission on Volcanic caves, 69, 11-12. Honda T., Tinsley J.C., 2016. Classification of lava tubes from Hydrodynamic models for active lava tube, filled lava tube and drained lava tube. 17th International Vulcanospeleology symposium in Hawaii, USA. Sponsored by the Commission on volcanic caves of the International Union of Speleology.Larson C.V., 1991. Nomenclatures of lava tube features. 6th International Symposium on Vulcanospeleology in Hawaii. Published by the National Speleological Society, 231-248.Laumanns M., 2013. Important Lava Tube Caves found in Dong Nai Province Southern Vietnam. e-NEWSLETTER, UIS Commission on Volcanic caves, 67, 13. Machado M., Lima E., 2014. Geotourism and sustainable development partnerships in the Azores Geopark. Abstract Book Workshop “Geoparks in volcanic areas: sustainable development strategies”, October 29th to November 1st. Terceira and Graciosa Islands, Azores Global Geopark, 45-48.Moreira Jasmine Cardozo, et al., 2014.Tourism and Volcanism in the Canary Islands, Spain. In Volcanic Tourist Destinations.Springer, Editors: Erfurt-Cooper, Patricia (Ed.). ISBN: 978-3-642-16190-2, 47-55.Nelson S.A., 2017. Volcanoes and Volcanic Eruptions.EENS 1110. Physical Geology.Tulane University. New Orleans, USA.Nguyen Duc Thang (Ed.), 1989. Geology and Mineral Resources of Ben Khe - Dong Nai sheet at scale 1:200,000. General Department of Geology and Minerals of Vietnam. Hanoi. Nunes, João Caros., 2014. The Azores Archipelago: Islands of Geodiversity.In Volcanic Tourist Destinations. Springer, Editors: Erfurt-Cooper, Patricia (Ed.). ISBN: 978-3-642-16190-2, 57-67.Nunes João Caros., 2014. Azores Geopark volcanoes and volcanic landforms. Valuating the Azorean geodiversity and geosites through the geotourism. Abstract Book Workshop “Geoparks in volcanic areas: sustainable development strategies”, October 29th to November 1st. Terceira and Graciosa Islands, Azores Global Geopark, 41-43.Ogawa T., 1993. On lava caves in Japan and vicinity.Proceedings of the Third International Symposium on Vulcanospeleology, 56- 73.Patricia Erfurt-Cooper, 2014. Volcanic Geo-heritage.Sustainable Tourism Development in Volcanic Regions: Geoparks, National Parks and World Heritage Sites. Abstract Book Workshop “Geoparks in volcanic areas: sustainable development strategies”, October 29th to November 1st. Terceira and Graciosa Islands, Azores Global Geopark, 23-25.Peterson D.W., Holcomb R.T., Tilling R.I., Christiansen R.L., 1994. Development of lava tubes in the light of observations at Mauna Ulu, Kilauea Volcano, Hawaii. Bulletin of Volcanology, 56, 343-360.